دور الإتصال التربوي في الحد من ظاهرة العنف المدرسي - بن ثابت ياسين; د/رحمون آدم (My University, 2023)
ملخص: أكثر الأمور تحديا في إدارة النظم التربوية المتنامية الحجم و التعقد هو تأسيس نظام فعال للاتصال و المحافظة على استمرارية فاعليته، فالاتصال من وظائف الإدارة الضرورية، و هو الوسيلة التي تنتقل عن طريقها المعاني و الأفكار من إنسان لآخر أو من جماعة لأخرى، ويختلف الاتصال حسب طبيعة المؤسسة أو الأشخاص ومن بين هذه المؤسسات نجد المؤسسة التربوية التي يقع فيها ما يسمى بالاتصال التربوي، إذ يكون اتصال مباشر وفعال بين الأستاذ والتلميذ حيث يساهم في تحقيق الأهداف المسطرة، فإذا كان الاتصال جيد وفعال بين الأستاذ والتلميذ فإن الأستاذ حتما يستطيع التأثير على أفكار وتوجهات التلميذ وسلوكاته وخاصة في هذه المرحلة وهي المراهقة، ومن بين هذه السلوكات، نجد السلوكات العدوانية التي انتشرت بشكل رهيب في الآونة الأخيرة في الأوساط العائلية والشوارع وخاصة في الوسط المدرسي الذي يعتبر نقطة التقاء واحتكاك الأفراد مع بعضهم البعض. تعد ظاهرة العنف بين طلبة المدارس من أكثر المشكلات المدرسة سلبية و انتشارا، و التي قد تعيق العمل التربوي التعليمي المتوقع من المدرسة و تجعلها بيئة غير ملائمة لتحقيق الأهداف التربوية المنطوبة بها، فظاهرة العنف المدرسي من الظواهر الرئيسية الأكثر شيوعا في المدراس و باتت تشكل عبئا ثقيلا على كاهل العاملين بها لتعاملهم اليومي مع هذه السلوكيات، و أصبحت مشكلة رئيسية لإدارة المدرسة و للمعلمين و المرشدين التربويين و الآباء و المختصين في مجال الصحة النفسية المدرسية. تعد المرحلة الثانوية مرحلة لاكتمال النمو الجسدي و العقلي للطالب لذلك تحتاج هذه المرحلة لمعاملة خاصة كما أم مطالب و فعاليات المدرسة الثانوية تتخطى كثيرا مطالب المدرسة الابتدائية و المتوسطة، و مع التنوع في مشكلات المراهقة و تنامي الآثار الناتجة عن تلك الممارسات على كافة الجوانب التحصيلية و التربوية للتلاميذ، توجب إلقاء المزيد من الاهتمام العلمي عبر دراسات و أبحاث، هذا للوقوف على الأسباب و الدوافع الحقيقية لهذه المشكلات. و انطلاقا من هذه المعطيات وقع اختيارنا لموضوع بحثنا وهذا لتسليط الأضواء على مختلف العوامل التي تقف وراء ظاهرة العنف المدرسي و السلوك العدواني الصادر عن التلاميذ في مرحلة الثانوية خاصة أنهم بفترة أو مرحلة المراهقة و التي تعتبر مرحلة صعبة في حياة الفرد لما يحدث فيها من تغيرات عقلية وجسمية. الكلمات المفتاحية: الإتصال التربوي ، الاتصالات غير اللفظية، العنف المدرسي، المشكلات السلوكية Abstract : The most challenging thing in managing educational systems of growing size and complexity is establishing an effective communication system and maintaining its continued effectiveness. Communication is one of the necessary management functions, and it is the means through which meanings and ideas are transmitted from one person to another or from one group to another. Communication varies according to the nature of The institution or persons. Among these institutions, we find the educational institution in which what is called educational communication occurs, as there is direct and effective communication between the professor and the student, which contributes to achieving the established goals. If the communication is good and effective between the professor and the student, then the professor can inevitably influence the ideas and directions of the student. And his behaviors, especially at this stage, which is adolescence, and among these behaviors, we find aggressive behaviors that have spread terribly recently in family circles, the streets, and especially in the school environment, which is considered the point of meeting and friction of individuals with each other. The phenomenon of violence among school students is one of the most negative and widespread school problems, which may hinder the educational work expected from the school and make it an inappropriate environment for achieving the educational goals assigned to it. The phenomenon of school violence is one of the most common major phenomena in schools and has become a heavy burden. On the shoulders of its employees because of their daily dealings with these behaviors, and it has become a major problem for the school administration, teachers, educational counselors, parents, and specialists in the field of school mental health. The secondary stage is a stage for the completion of the student’s physical and mental development, so this stage needs special treatment, as the demands and activities of the secondary school greatly exceed the demands of the primary and middle school, and with the diversity in the problems of adolescence and the growing effects resulting from these practices on all academic and educational aspects. For students, more scientific attention must be paid through studies and research, in order to find out the real causes and motives for these problems. Based on these data, we chose the topic of our research to shed light on the various factors behind the phenomenon of school violence and aggressive behavior by students in the secondary stage, especially since they are in the period of adolescence, which is considered a difficult stage in an individual’s life due to the mental and physical changes that occur in it. . Keywords: educational communication, non-verbal communication, school violence, behavioral problems
دراسة ميدانية على عينة من ثانويات ولايات الأغواط